Effect of Eplerenone Treatment in Patients with Central Serous Retinopathy: A Double-Blind Randomized Clinical Trial - Mohammadreza Akhlaghi; Alireza Dehghani; Farzan Kianersi; Mohammad Reza Khalili; Mohammad Tohidi; Hamidreza Jahanbani-Ardakani (Journal of Current Ophthalmology, 2024)
Purpose To evaluate the efficacy of eplerenone in central serous chorioretinopathy (CSCR) patients in a clinical trial design. Methods In this double-blind clinical trial, naive acute. CSCR patients were divided into two groups: treatment with eplerenone 25 mg daily in the 1st week followed by 50 mg for the next 3 weeks and placebo group. Best-corrected visual acuity (BCVA), central macular thickness (CMT), macular volume (MV), and choroidal thickness (CT) were measured before and after 1 month of the intervention using the optical coherence tomography technique. Results Thirty-one CSCR (male: 23, female: 8) and 25 CSCR patients (male: 18, female: 7) with the mean age of 35.65 ± 5.94 and 37.08 ± 6.41 years were recruited and divided randomly into treatment and placebo groups, respectively. BCVA improved significantly in the treatment group (from 0.28 ± 0.26 to 0.11 ± 0.14, P = 0.002) compared with the placebo group (from 0.31 ± 0.26 to 0.21 ± 0.14, P = 0.052). Although CT, CMT, and MV improved significantly in each group, there were no significant differences between the groups. Conclusion In this study, we found favorable short-term clinical effects of eplerenone in acute CSCR patients, showing the pivotal role of mineralocorticoid receptors in the retina.